2022
DOI: 10.3389/fpsyg.2022.804753
|View full text |Cite
|
Sign up to set email alerts
|

Basic Motor Competencies of 6- to 8-Year-Old Primary School Children in 10 European Countries: A Cross-Sectional Study on Associations With Age, Sex, Body Mass Index, and Physical Activity

Abstract: Basic motor competencies (BMC) are a prerequisite for children to be physically active, participate in sports and thus develop a healthy, active lifestyle. The present study provides a broad screening of BMC and associations with age, sex, body mass index (BMI) and extracurricular physical activity (PA) in 10 different European countries. The different country and regional contexts within Europe will offer a novel view on already established BMC associations. The cross-sectional study was conducted in 11 regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 52 publications
(81 reference statements)
3
19
1
Order By: Relevance
“…Variations in BMC between the subsamples were even higher in this study than in a previous study that examined only first and second graders (Wälti et al 2022). The transition phase from second to third grade seems to determine whether a child's development is age-appropriate or delayed (Augste and Jaitner 2010).…”
contrasting
confidence: 65%
See 1 more Smart Citation
“…Variations in BMC between the subsamples were even higher in this study than in a previous study that examined only first and second graders (Wälti et al 2022). The transition phase from second to third grade seems to determine whether a child's development is age-appropriate or delayed (Augste and Jaitner 2010).…”
contrasting
confidence: 65%
“…Few studies compared motor competence levels and associates over several countries or regions. They found better fine and gross motor skills in northern European countries than in southern (Haga et al 2018) and strong differences in SM tasks across European countries in first and second grade children (Wälti et al 2022). Differences in motor competence levels between Brazilians and Portuguese children were dependent on the sex (Flôres et al 2021) or on extracurricular PA when comparing Portuguese and U.S. children (Luz et al 2019).…”
mentioning
confidence: 92%
“…Sex differences in motor performance have often been investigated (Barnett et al, 2016;Katić et al, 2013;Kokštejn et al, 2017;Latorre-Román et al, 2016;Morris et al, 1982). In general, boys performed better in object movement while girls performed better in self-movement (Wälti et al, 2022). Morris et al (1982) found that boys were superior to girls at 3-6 years old on speed run tests, and girls were superior to boys at age 6 on a balance test, suggesting that sex differences in motor performance are already present as early as in the preschool years.…”
Section: Sex Differencesmentioning
confidence: 99%
“…They reported that 7-or 8-year-olds showed a higher index of coactivation in maturation of the nervous system compared with 10-year-old children. In addition, sex differences in basic motor competency including running speed, object movement, and self-movement were already found among preschool children, and boys performed better in object movement, whereas girls performed better in self-movement (Barnett et al, 2016;Morris et al, 1982;Wälti et al, 2022).…”
mentioning
confidence: 92%
See 1 more Smart Citation